Pemahaman Wanita Islam Kg. Manjoi, Perak Terhadap Hukum Jual Beli Barang Perhiasan Daripada Emas Secara Ansuran - Jamaluddin, Farhatun Atmam; Mohamad, Shamsiah (Jurnal Fiqh, 2012)
Community Kg. Manjoi mostly involved with the women in the community of Kg. Manjoi are mostly involved in buying and selling jewellery. Sometimes they buy it in instalments, cash, trade in, and so on. This study aims to understand the law of buying and selling gold jewellery from the Islamic perspective. In addition, this study aims to determine the level of understanding of Muslim women in Kg. Manjoi towards purchasing gold jewellery by instalments. Data were collected using the documentation and survey method. The data for the survey method in the current study were collected by means of a questionnaire administered on a sample of 80 respondents in an attempt to identify the relationship between the understanding of Muslim women in Kg. Manjoi towards purchasing gold jewellery by instalments and stream education and level of education. Data were analysed by using SPSS 20.0. This study finds that the understanding of Muslim women in Kg. Manjoi towards purchasing gold jewellery by instalments is at a low level. Most of them are little concerned about the law relating to selling and purchasing gold jewellery.